Mixtoscutella ovata - Grischenko, Andrei V.; Gordon, Dennis P.; Taylor, Paul D.; Kuklinski, Piotr; Denisenko, Nina V.; Spencer-Jones, Mary E.; Ostrovsky, Andrew N. (Zenodo, 2022)
Mixtoscutella ovata (Smitt, 1868) (Figs 27, 33G) Cellepora ovata Smitt, 1868a, p. 31, pl. 28, fig. 197. Cellepora ovata : Smitt 1868b, p. 485; Hincks 1877, p. 105, pl. 11, fig. 5. Rhamphostomella ovata : Nordgaard 1906, p. 32, 41, pl. 4, fig. 56; Kluge 1962, p. 540, fig. 377; 1975, p. 657, fig. 377; Osburn 1912a, p. 245, pl. 26, fig. 63; 1933, p. 54, pl. 11, figs 5, 6; 1952, p. 432, pl. 50; Androsova 1958, p. 170, fig. 101; Gostilovskaya 1978, p. 227, fig. 143; Winston & Hayward 2012, p. 121, fig. 77; Grischenko 2013, p. 177, figs. 1q–r. Discopora ovata : Nordgaard 1918, p. 78. Additional references. Rhamphostomella ovata : Kluge 1908a, p. 533; 1928, p. 257; 1929, p. 22; 1961, p. 141; Osburn 1936, p. 542; 1955, p. 38; Gostilovskaya 1957, p. 455; 1968, p. 70; Hansen 1962, p. 40; Powell & Crowell 1967, p. 343; Powell 1968a, p. 2312; 1968b, p. 257; Gontar 1980, p. 18; 1990, p. 132; 1993b, p. 202; 1994a, p. 145; 2010, p. 153; Denisenko 1988, p. 13; 1990, p. 39; 2008, p. 187; 2011, p. 14; 2013, p. 184; Gontar & Denisenko 1989, p. 354; Grishankov 1995, p. 48; Kubanin 1997, p. 123; Gontar et al . 2001, p. 195; Shunatova & Ostrovsky 2001, p. 115, 118; Shunatova & Nielsen 2002, p. 263, fig. 1b; Grischenko 2002, p. 115; Kuklinski 2002b, p. 203; 2009, p. 228; Denisenko & Kuklinski 2008, p. 48; Ostrovsky 2009, p. 175, fig. 78a; 2013, p. 8, figs 1.11c, 2.41a; Denisenko et al . 2016, p. 366. Material examined. Lectotype : SMNH-Type-9303, six fragments from one colony, Swedish Arctic Expedition, July 1861, Red Bay, west Spitsbergen, Svalbard and Jan Mayen, depth 64 m, mud. Paralectotype : SMHM-Type-9305, small colony growing on eroded fragment of another cheilostome, Swedish Arctic Expedition, September 1861, Advent Bay, Isfjord, west Spitsbergen, Svalbard and Jan Mayen, depth 35 m, mud with stones. NHMUK 1911.10.1.1581A, one colony, ex Swedish Museum Natural History, from F.A. Smitt Collection, Spitsbergen. NHMW 44378, one colony fragment, Kola Haven, collector H. Kluge [before 1907]. ZIRAS 36 /50120, ...